ALTERNATIVE DESIGN OF PIDEKSO DAM DIVERSION TUNNEL, WONOGIRI REGENCY, CENTRAL JAVA PROVINCE - Iqbal Huseiny, Moh.
Pidekso Dam is one of the dams in Wonogiri Regency, Central Java Province with a watershed area of 56.79 km2 which is projected to meet irrigation and raw water needs. One of the construction processes of the Pidekso Dam is the process of circumventing the river with a conduit diversion tunnel and a cofferdam. The capacity of the original design of the conduit amounted to only 17.6% of the planned flood discharge. In addition, the dimensions of the original conduit are 1- hole horseshoe-shaped which has the potential to completely close the flow of water downstream when plugging the conduit. Therefore, an alternative building design planning is needed by adjusting the actual conditions in the field. Re-planning includes hydrological analysis based on the technical manual of flood discharge on dams and hydraulic analysis of the conduit with the help of HY-8 software. From the calculation results, an alternative dimension of the plan is a double box culvert measuring 3 m x 3 m x 2 holes with a maximum outflow discharge of 152.92 m3/s with maximum flood elevation at +171.32 m. The reinforcement used on the conduit is D25-200 on the upper slab, D19-150 on the side slab, D25-150 on the bottom slab, and D16-150 for shrinkage/divider reinforcement. The dimensions of the cofferdam were selected zonal type of inclined core with a slope of 1:3 and the summit elevation of the cofferdam was at +173 m. The budget cost for the building is about IDR 64 billion.